Evaluation of serum thyroid‐stimulating hormone as indicator for fine‐needle aspiration in patients with thyroid nodules. Issue 4 (9th April 2014) - Choi, Ji Soo; Nam, Chung Mo; Kim, Eun‐Kyung; Moon, Hee Jung; Han, Kyung Hwa; Kwak, Jin Young
Abstract: Background: Recently, it has been reported that the risk of thyroid malignancy increases with increasing concentrations of serum thyroid‐stimulating hormone (TSH). The purpose of this study was to determine whether or not serum TSH can be a predictor for thyroid malignancy when considering the relevant ultrasound features and clinical risk factors. Methods: This retrospective study included 1200 euthyroid patients with 1269 thyroid nodules who underwent ultrasound‐guided fine‐needle aspiration (FNA) biopsy between January and June 2009. Serum TSH, ultrasound feature, and clinical parameters were compared according to final diagnosis. Subgroup analyses were performed according to nodule size. Results: Serum TSH did not show a positive association with malignancy for all nodules and the micronodule subgroup in multivariate analysis, although they showed significant association with thyroid malignancy for the macronodule subgroup. For all nodules and the 2 subgroups, suspicious ultrasound features and younger age were significantly associated with malignancy in univariate and multivariate analyses. Conclusion: Our study suggests that TSH alone is not as useful as ultrasound features in deciding whether or not to perform FNA in patients with micronodules. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 498–504, 2015